Hepatotoxicity Comparison of Crude and Licorice-Processed Euodiae Fructus in Rats With Stomach Excess-Cold Syndrome - Min Zhang; Min Zhang; Meng Gao; Shanshan Wu; Lifen Zhou; Lan Cao; Rifa Qiao; Minyong Zhong; Lin Yang; Jinbin Yuan (Frontiers Media S.A., 2021)
In recent years, drug-induced liver injury (DILI) has become an important issue of public health. Euodiae Fructus (EF) is a commonly used herb with mild toxicity in clinic, and large doses of EF can cause significant liver damage. Licorice processing might reduce the hepatotoxicity of CEF (crude EF), but up to now, studies on the hepatotoxicity of EF have been hardly reported, let alone its material basis and mechanism of detoxification by licorice processing. This work firstly established a stomach excess-cold syndrome animal model induced by intragastric administration of cold Zhimu (Anemarrhena asphodeloides Bge). Secondly, multiple approaches and indexes were used to evaluate the hepatotoxicity of the drugs in the rats including general behavior, biochemical analysis, protein expressions, and histopathological examination. Thirdly, the hepatotoxicity of three doses of three CEF and LPEF (licorice-processed EF) extracts was systematically investigated, and the hepatotoxicity differences were analyzed and compared comprehensively among the three extracts, three doses, and CEF and LPEF. Finally, the connotation of detoxification of EF by licorice processing was preliminarily discussed according to the changes in toxic components after processing, toxicological characteristics, and TCM (traditional Chinese medicine) theory. All extracts of EF were found to have dose-dependent hepatotoxicity, and the toxicity was in the descending order of water extract, ethanol extract, and volatile oil. The hepatotoxic mechanism of EF may be related to peroxidation damage, inflammatory factor, and mitochondrial injury. The CEF hepatotoxicity can be significantly reduced by licorice processing. EF should be safe for short-term use at pharmacopeial dose under the guidance of the TCM theory. The detoxification mechanism is probably related to the reduction of toxic components and antagonistic action of licorice.